Pulmonary artery vegetation in a pediatric patient with ventricular septal defect: a case report - Haryo Aribowo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2017)
ABSTRACTIntroduction: Infective endocarditis (IE) is one of the congenital heart disease complications which is frequently seen in ventricular septal defects (VSD). The Duke criteria are the diagnostic criteria for IE. One of the major criteria is evidence of vegetation. In VSD complicated with IE, vegetation is frequently found on the opening of the defect, on the right ventricular side of the opening, on the tricuspid valve, and less frequently it is found on the pulmonary valve. Vegetation found in the lumen of pulmonary artery is rarely reported.Case report: A 6 years old boy was consulted with congenital heart disease. His chief complaint was shortness of breath. He came with unspecific signs and symptoms with a history of frequent hospitalization due to pneumonia and paleness. Chest X-ray showed enlargement of heart chambers. Transthoracic echocardiography (TTE) revealed moderate size VSD and multiple vegetation on right ventricle outflow tract, pulmonary artery valve, and inside the lumen of main pulmonary artery and right pulmonary artery. The blood culture showed a positive result for S. viridans. He was treated with parenteral antibiotic and operated on later. We successfully performed evacuation of the vegetation and VSD closure.Conclusion: We reported a rare case of pulmonary artery vegetation in a boy with moderate VSD that we treated with combination of parenteral antibiotic followed by successful surgical vegetation evacuation and VSD closure.ABSTRAKPembukaan: Endokarditis infektif merupakan salah satu komplikasi penyakit jantung bawaan yang sering menyertai defek septum ventrikel (VSD). Kriteria Duke merupakan kriteria diagnosis untuk endokarditis infektif. Salah satu kriteria mayor nya adalah bukti adanya vegetasi. Pada VSD dengan komplikasi endokarditis infektif, vegetasi sering ditemukan pada pembukaan dari defek, pada ventrikel kanan, pada katup trikuspid, dan yang paling jarang pada katup pulmonalis. Vegetasi pada arteri pulmonalis jarang dilaporkan.Laporan kasus: Anak laki-laki berusia 6 tahun dikonsultasikan dengan penyakit jantung bawaan. Keluhan utamanya adalah sesak nafas. Pasien datang dengan tanda dan gejala yang tidak khas dengan riwayat rawat inap berulang karena pneumonia dan pucat. X-ray dada menunjukkan pembesaran ruangan-ruangan jantung. Transthoracic echocardiography menunjukkan VSD berukuran sedang dan vegetasi multiple pada right ventricle outflow track, katup pulmonalis, dan didalam lumen arteri pulmonalis komunis dan arteri pulmonalis kanan. Kultur darah positif untuk S. viridans. Pasien menerima antibiotik parenteral dan menjalani pembedahan setelahnya. Kami berhasil melakukan evakuasi vegetasi dan penutupan VSD.Kesimpulan: Kami melaporkan kasus vegetasi arteri pulmonal pada anak laki-laki dengan VSD sedang yang kami terapi dengan kombinasi antibiotik parenteral diikuti dengan pembedahan evakuasi vegetasi dan penutupan VSD.Keywords: pulmonary artery; vegetation; ventricular septal defect; infective endocarditis; surgery